The different effects of preheating and heat treatment on the surface microhardness of nanohybrid resin composite - Brelian Elok Septyarini; Irfan Dwiandhono; Dian N. Agus Imam (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: A composite resin is used as restorative material in dentistry because it has the same colour as dental enamel, is easy to use in an oral cavity and offers good biocompatibility. Based on the size of filler, composite resin is divided into types, one of which is a composite resin nanohybrid. An important mechanical property of restorative material is microhardness. The mechanical properties of restorative material is highly affected by both polymerisation and heating process. There are many methods to improve composite resin’s microhardness, including preheating and heat treatment. Purpose: The purpose of this study was to evaluate different effects of preheating and heat treatment on the microhardness of nanohybrid composite resin. Methods: This study is an experimental laboratory research with post-test-only group design. Samples were divided into six groups: preheating groups at temperatures of 37oC and 60oC, heat treatment groups at temperatures of 120oC and 170oC, a negative control group and a positive control group. Afterwards, the resulting data were analysed using one-way ANOVA. Results: The result based on the one-way ANOVA test indicated that there was a difference in microhardness in each group with a significance of 0.000 (p<0.005) between preheating and heat treatment. Conclusion: The conclusion of this study was the best microhardness of composite resin nanohybrid is the heat treatment group at temperature 170oC.